(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
This article focuses on the rapid development of the physical and mental health of these segments of the population, which is the first priority in the field of sports to improve the culture and livelihoods of generations of the state and society. Physical education and sports stimulate the mental and spiritual well-being of children and adolescents, as well as the formation of feelings of patriotism and patriotism.